Energy Self-Sufficient Livestock Farm as the Example of Agricultural Hybrid Off-Grid System - Grzegorz Augustyn (MDPI AG, 2021)
Contemporary agriculture has become very energy-intensive and mainly uses electricity, which is needed for technological processes on livestock farms. Livestock faeces are burdensome for the environment due to the release of methane into the atmosphere. This article presents the concept of a self-sufficient livestock farm as an off-grid energy circuit that is a part of the agricultural process. The key idea is to obtain an energy flow using the concept of a smart valve to achieve a self-sufficient energy process based on a biogas plant, renewable energy sources, and energy storage. During the production process, a livestock farm produces large amounts of waste in the form of grey and black manure. On the one hand, these products are highly harmful to the environment, but on the other, they are valuable input products for another process, i.e., methane production. The methane becomes the fuel for cogeneration generators that produce heat and electricity. Heat and electricity are partly returned to the main farming process and partly used by residents of the area. In this way, a livestock farm and the inhabitants of a village or town can become energy self-sufficient and independent of national grids. The idea described in this paper shows the process of energy production combining a biogas plant, renewable energy sources, and an energy storage unit that enable farmland to become fully self-sufficient through the energy flow between all constituents of the energy cycle being maintained by a smart valve.